Comparison of Thematic Structure and Progression between English and Indonesian Exposition Texts Written by Undergraduate Students of UPI (Rhetorical Study) - Undayasari, Dwi; Saleh, Mursid (Universitas Negeri Semarang, 2018)
The research aimed to analyze the realization of thematic structure and progression in English and Indonesian exposition texts and explain the contribution of thematic structure and progression to the cohesion and coherence in English and Indonesian exposition texts. The research also aimed toexplain the differences and similarities between English and Indonesian in terms of coherence and schematic structure of the exposition text. Descriptive-qualitative design was used in this research considering of the objectives of the research. The sample of the research was taken from collecting English and Indonesian exposition texts written by undergraduate students of UPI. This study used the theory of Theme system developed by Halliday (1994), Eggins (1994; 2004), the theory of thematic progression proposed by Eggins (1994; 2004 as the framework to analyze the data) and the theory of coherence analysis proposed by Thornbury (2005). To figure out the differences and similarities between English and Indonesian exposition texts, it can be seen from the level of coherence (level of clause, sentence, and paragraph) and schematic structure of text. In level of clause, it can be seen from thematic structure and progression analysis. The result showed that the students write effectively orient the reader to what their texts are about either in English or Indonesian texts. Students used reiteration as much as zigzag pattern in their English in order to maintain the focus and reinforced the arguments in their texts but in Indonesian texts, students more reinforced the argument than maintain the focus to the arguments in their Indonesian texts. In level of sentence, the finding showed that English texts tended to use deductive style rather than inductive and mix style. While in Indonesian text, the use of inductive and mix types of paragraphs in Indonesian texts were more than in English texts. In level of paragraph, multiple paragraphs were dominant in students’ English texts but some Indonesian texts were managed unwell. Concerning in term of schematic structure, most of English texts consisted of the three generic structures of exposition texts but there were some Indonesian texts that was not given the reiteration or conclusion at the last paragraph.